2020
DOI: 10.20414/jb.v13i1.196
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Effectivity on Hepar and Reproductive Organ Recovery Male Mice (Mus musculus L) after Methoxychlor Exposure

Abstract: Methoxychlor (MXC) is an insecticide (DDT derivates) that has the potential for bioaccumulation in mammal and causes a disruptive effect on the hepar and reproductive system. This study was done to find out the benefits of curcumin as a natural ingredient to overcome the negative impact of Methoxychlor (MXC) on hepar and male reproductive organ of Balb’C mice (Mus musculus L). The study was carried out in a Completely Randomized Design (CRD) Posttest Only Control Group Design used four treatments and six repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A randomized clinical trial on infertile men demonstrated a significant increase in the total sperm count, sperm concentration, and motility levels along with the remarkable enhancement in the plasma levels of total antioxidant capacity, malondialdehyde (MDA), C‐reactive protein, and TNF‐α following curcumin administration (Alizadeh et al, 2018). It has been shown that curcumin has ameliorated testis damage and improved the abnormal sperm parameters induced by different chemical substances (Chaithra et al, 2020; Mahriani, Fajariyah, & Utami, 2020; Mohamed, Thabet, & Abdel‐hafez, 2017; Salem, Alnahdi, & Ibrahim, 2017). Chaithra et al (2020) revealed that curcumin in a dose of 100 mg/kg due to its antioxidant and antiapoptotic properties improves the toxic effect of fluoride and sodium fluoride on the reproductive system of male Wistar rats.…”
Section: Methodsmentioning
confidence: 99%
“…A randomized clinical trial on infertile men demonstrated a significant increase in the total sperm count, sperm concentration, and motility levels along with the remarkable enhancement in the plasma levels of total antioxidant capacity, malondialdehyde (MDA), C‐reactive protein, and TNF‐α following curcumin administration (Alizadeh et al, 2018). It has been shown that curcumin has ameliorated testis damage and improved the abnormal sperm parameters induced by different chemical substances (Chaithra et al, 2020; Mahriani, Fajariyah, & Utami, 2020; Mohamed, Thabet, & Abdel‐hafez, 2017; Salem, Alnahdi, & Ibrahim, 2017). Chaithra et al (2020) revealed that curcumin in a dose of 100 mg/kg due to its antioxidant and antiapoptotic properties improves the toxic effect of fluoride and sodium fluoride on the reproductive system of male Wistar rats.…”
Section: Methodsmentioning
confidence: 99%